Detection of Enterobacteriaceae in fresh chicken eggs for human consumption in the city of Valledupar, Cesar (Colombia) - Araujo-Guerra, Álvaro Vicente; Fragoso-Castilla, Pedro José; Peña-Guillin, Alex Efraín; Pineda-Quintero, Álvaro; Mejía-Arbeláez, Jesús Federico (Spei Domus, 2019)
Introduction: the Enterobacteriaceae family is the largest and most heterogeneous group of gram-negative bacilli, many of them of public health importance, associated among others with the consumption of fresh eggs, even those with intact and clean skin. Methodology: 200 eggs were obtained by sampling at 10 commercial outlets in the city of Valledupar, Cesar (Colombia), of which the shell and yolks were studied using a pre-enrichment protocol, selective enrichment and, therefore, a selective medium. differential to determine the presence of enterobacteria. Results: the presence of enterobacteria in the shell and yolks was determined in 31% of the eggs, as well as 15.5% with contamination with other microorganisms. The presence of the fungus Aspergillus fumigatus was also proven. Conclusions: the results demonstrate the presence of pathogenic agents in eggs marketed in the studied area, and the consequent need to intervene to protect consumers’ health. It is recommended that public health agents take action to intervene and conduct research in order to find out about potential health risks, as well as document cases associated with the consumption of these eggs.